2004
DOI: 10.3390/i5050239
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Orbital and Density Functional Study of the Formation, Charge Transfer, Bonding and the Conformational Isomerism of the Boron Trifluoride (BF3) and Ammonia (NH3) Donor-Acceptor Complex

Abstract: :The formation of the F 3 B-NH 3 supermolecule by chemical interaction of its fragment parts, BF 3 and NH 3 , and the dynamics of internal rotation about the 'B-N' bond have been studied in terms of parameters provided by the molecular orbital and density functional theories. It is found that the pairs of frontier orbitals of the interacting fragments have matching symmetry and are involved in the charge transfer interaction. The donation process stems from the HOMO of the donor into the LUMO of the acceptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 45 publications
0
13
0
4
Order By: Relevance
“…Although, more recently, there are also claims of partitioning the total SCF energy into one-and two center components in ab initio methods [20], but such fuzzy atom dissection of total energy appears to calculate the total one-and two-center interaction energies only and decomposition of such energy terms into meaningful physical components are, probably, yet to be furnished [20]. We have recently demonstrated that the Pople's energy partitioning scheme can be invoked in the significant elucidation of the origin of the barrier to the physical process of inversion [21,22] and intramolecular rotation [23,24], and such an effort is a meaningful venture. In the present venture, we shall invoke the energy partitioning scheme of Pople in the elucidation of the origin of barrier to internal rotation of hydrogen peroxide (H 2 O 2 ) and its analogue fluorine peroxide (F 2 O 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although, more recently, there are also claims of partitioning the total SCF energy into one-and two center components in ab initio methods [20], but such fuzzy atom dissection of total energy appears to calculate the total one-and two-center interaction energies only and decomposition of such energy terms into meaningful physical components are, probably, yet to be furnished [20]. We have recently demonstrated that the Pople's energy partitioning scheme can be invoked in the significant elucidation of the origin of the barrier to the physical process of inversion [21,22] and intramolecular rotation [23,24], and such an effort is a meaningful venture. In the present venture, we shall invoke the energy partitioning scheme of Pople in the elucidation of the origin of barrier to internal rotation of hydrogen peroxide (H 2 O 2 ) and its analogue fluorine peroxide (F 2 O 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Исторически первым соединением такого рода, полученным еще в начале XIX века, является трифтороамминбор, BF 3 ←NH 3 [2]. Он обладает этаноподобной структурой, которая в последние десятилетия активно изучалась методами рентгеноструктурного анализа [3], микроволновой спектроскопии [4,5], дифракции нейтронов и ЯМР [6,7], а также с помощью расчетных DFT и ab initio приближений [6,[8][9][10]. Сама молекула трифтороамминбора характеризуется заторможенным вращением; при этом минимуму на поверхности потенциальной энергии (ППЭ) отвечает шахматный конформер, а переходному состояниюзаслоненная форма [3][4][5][6][7][8][9][10].…”
Section: Introductionunclassified
“…Таким образом, экспериментальные факты весьма противоречивы. В то же время расчетное значение высоты барьера внутреннего вращения в трифтороамминборе невелико; в рамках DFT приближения при 0 К оно составляет 0.73 ккал/моль [9], а при использовании метода МР2 -1.17 ккал/моль (408 см -1 ) [11]. При этом число методов, использованных для расчета относительной стабильности конформеров трифтороамминбора, весьма ограничено.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The bond energy can be conveniently evaluated invoking the energy partitioning technique of Fischer and Kollmar [43]. We have already demonstrated that the energy partitioning approach is a meaningful venture in locating the origin of barrier to the physical process of inversion [36,37] and intra molecular rotation [44,45] of molecules. We have, therefore, taken up a detailed study of the dipole correlation of the electronic structure of the conformations, including the equilibrium one, of water molecule between angular to linear shapes.…”
Section: Dipole Moment As a Probe Of The Electronic Structure Of Watementioning
confidence: 99%